Pengaruh Aktivitas Fisik terhadap Pola Tidur Penderita Rematik di Posyandu Lansia Sumber Pucung Kabupaten Malang - Dhea Ayu Sukmawati; Ratna Roesardhyati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Rheumatism in the elderly can cause chronic pain that affects the quality of sleep. One of the factors influencing the sleep pattern of elderly patients with rheumatism is the level of physical activity. Insufficient physical activity can worsen joint stiffness and increase sleep disturbances. This study aims to examine the effect of physical activity on sleep patterns in elderly rheumatism patients at the Sumber Pucung Elderly Posyandu, Malang Regency. This study is a quantitative study with an analytical correlational design using a cross-sectional approach. The population of this study consisted of all elderly rheumatism patients at the Sumber Pucung Elderly Posyandu, totaling 33 people. The sampling technique used was total sampling. The study was conducted from July 20 to 27, 2025. Data collection instruments used the Global Physical Activity Questionnaire (GPAQ) and the Pittsburgh Sleep Quality Index (PSQI) questionnaires. The results showed that most respondents (90.9%) had low physical activity and all respondents (100%) had poor sleep patterns. The simple linear regression test yielded a significance value of p = 0.479 (p > 0.05) and R Square = 0.016, indicating no significant effect of physical activity on sleep patterns. Based on these results, it is expected that elderly rheumatism patients can increase physical activity according to their abilities to help maintain sleep quality, and Posyandu officers can provide education and elderly exercise programs appropriate for rheumatism conditions.